2010
DOI: 10.1007/s10773-010-0461-8
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Quantum Information Splitting with Six-Photon Cluster States

Abstract: We propose a scheme for hierarchical quantum information splitting with the recently realized six-photon cluster state (Lu et al. in Nat. Phys. 3:91, 2007), where a Boss distributes a quantum secret (quantum state) to five distant agents who are divided into two grades. Two agents are in the upper grade and three agents are in the lower grade. An agent of the upper grade only needs the collaboration of two of the other four agents for getting the secret, while an agent of the lower grade needs the collaboratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In 2008, Murlidharan and Panigrahi showed that the cluster state can be utilized for QIS [24]. QIS of an arbitrary three-qubit state can be realized by using the cluster states [25], the entangled states and the Bell state [26], the four-qubit cluster state and the GHZ-state [27], the five-qubit cluster state and the GHZ-state [28], the six-qubit entangled state [29], and the seven-qubit entangled state [30,31]. After Hillery et al demonstrated that GHZ states could be used for QIS (QIS), QIS has been investigated more often.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Murlidharan and Panigrahi showed that the cluster state can be utilized for QIS [24]. QIS of an arbitrary three-qubit state can be realized by using the cluster states [25], the entangled states and the Bell state [26], the four-qubit cluster state and the GHZ-state [27], the five-qubit cluster state and the GHZ-state [28], the six-qubit entangled state [29], and the seven-qubit entangled state [30,31]. After Hillery et al demonstrated that GHZ states could be used for QIS (QIS), QIS has been investigated more often.…”
Section: Introductionmentioning
confidence: 99%
“…This scheme drew considerable attention of the quantum communication community as the teleportation has no classical analog. Since the pioneering work of Bennett et al a large number of teleportation schemes and their applications have been reported [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. These teleportation schemes can be primarily classified into two broad classes: a) Perfect teleportation schemes [1,2] and b) Probabilistic teleportation schemes [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Till recent past all the studies on multi-party quantum teleportation were restricted to symmetric quantum information splitting where all the receivers were equally capable to recover the unknown quantum state sent by the sender (Alice). Recently the concept of asymmetric quantum information splitting is introduced by Wang et al [9,10,11]. In their scheme Boss (Alice) distributes a quantum state among several agents who are spatially separated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these schemes can be viewed as variants of teleportation.Recently, a few hierarchical versions of already existing aspects of quantum communication (variants of teleportation) have been proposed. Specifically, hierarchical quantum information splitting (HQIS) [11,12,14,15], hierarchical quantum secret sharing (HQSS) [12], hierarchical dynamic quantum secret sharing (HDQSS) [16], etc., have been proposed in the recent past. It is also shown that these schemes have enormous practical importance (for a detailed discussion on the interesting applications of these schemes see Sec.…”
mentioning
confidence: 99%